Gene Expression Profiling of Systems Involved in the Metabolism and the Disposition of Xenobiotics: Comparison between Human Intestinal Biopsy Samples and Colon Cell Lines - Bourgine, Joanna; Billaut-Laden, Ingrid; Happillon, Mélanie; Lo-Guidice, Jean-Marc; Maunoury, Vincent; Imbenotte, Michel; Broly, Franck (Drug metabolism and disposition, 2012)
Intestinal cell lines are used as in vitro models for pharmacological and toxicological studies. However, a general report of the gene expression spectrum of proteins that are involved in the metabolism and the disposition of xenobiotics in these in vitro systems is not currently available. To fill this information gap, we systematically characterized the expression profile of 377 genes encoding xenobiotic-metabolizing enzymes, transporters, and nuclear receptors and transcription factors in intestinal mucosa (ileum, ascending colon, transverse colon, descending colon, and rectum) from five healthy subjects and in five commonly used intestinal cell lines (Caco-2, C2BBe1, HT29, T84, and FHC). For this, we performed a quantitative real-time reverse transcription-polymerase chain reaction analysis using TaqMan low-density arrays and analyzed the results by different statistical approaches: Spearman correlation coefficients, hierarchical clustering, and principal component analysis (PCA). A large variation in gene expression spectra was observed between intestinal cell lines and intestinal tissues. Both hierarchical clustering and PCA showed that two distinct clusters are visible, of which one corresponds to all cultured cell lines and the other to all intestinal biopsies. The best agreement between human tissue and the representative cell line was observed for human colonic tissues and HT29 and T84 cell lines. Altogether, these data demonstrated that gene expression profiling represents a new valuable tool for investigating in vitro and in vivo expression level correlation. This study has pointed out interesting expression profiles for various colon cell lines, which will be useful for choosing the appropriate in vitro model for pharmacological and toxicological studies.